Feeling Ridiculous and the Emotion of Shame in Physical Experiences During Analysis - Carzedda, Giuseppe (Bioenergetic Analysis, 2015)
In this article, a clinical case is discussed according to Bioenergetic Analysis, focusing on the theme of shame and its presence in the patient’s inner experience of feeling ridiculous when carrying out physical exercise proposed during psychotherapy. Two aspects of the therapeutic process are highlighted: first, how the elaboration of this feeling can begin at the very early stages of therapy and second, how within dyadic analysis, the resulting complex and intense affective valences implied can render the approach to such a task quite problematic. Such difficulties lead to the reconsideration of the role of the emotion of shame. Generally, it must be recognized as an integral part of the process of the individual’s psychological development; the relevance of intersubjectivity within the analytic relationship is rendered even more evident. From this theoretical/clinical perspective, considerations derived from a phenomenological approach are recognized as having particular importance, as even imagined looks can assume a central relevance along the two-way relationship bridge that unites the therapist with the patient.